1989
DOI: 10.1111/j.1365-2621.1989.tb05960.x
|View full text |Cite
|
Sign up to set email alerts
|

Debittering Mechanism in Bitter Peptides of Enzymatic Hydrolysates from Milk Casein by Aminopeptidase T

Abstract: The bitter peptide fraction present in casein hydrolysates obtained by using three proteases (subtilisin, papain and trypsin) was treated with aminopeptidase T from 7'hennus aquaticus YT-1. The bitterness of the bitter peptide fraction could be decreased, and it sometimes disappeared completely, with an increase in free amino acids. The percentages of total free amino acids released from each bitter peptide fraction (subtilisin, papain and trypsin) by aminopeptidase digestion for 20 hr were approximately ll%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…Currently, there are number of reports of aminopeptidase used efficiently for removal of bitterness of protein hydrolysates [33,34]. However, the real challenge is to set up a single step enzymatic reaction to produce debittered protein hydrolysate.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are number of reports of aminopeptidase used efficiently for removal of bitterness of protein hydrolysates [33,34]. However, the real challenge is to set up a single step enzymatic reaction to produce debittered protein hydrolysate.…”
Section: Resultsmentioning
confidence: 99%
“…• carboxypeptidase (Umetsu and Ichishima, 1983), aminopeptidase T ( Minagawa et al, 1989), aminopeptidase II (Matsuoka et al, 1991), aminopeptidl1se N (Tan et al, 1993), and with endopeptidases (Baankreis, 1992), have all been reported. Basically, exopeptidases that are able to hydrolyze proline-containing peptides play a very important role, either by direct degradation of proline-containing peptides that often possess a bitter taste (Leadbeater and Ward, 1987) or indirectly by removing the blockage (proline residue) that blocked further degradation of such peptides by general exopeptidases.…”
Section: Introductionmentioning
confidence: 99%
“…The most systematic studies have been carried out on hydrolysates of casein, which is particularly prone to yielding bitter peptides. Aminopeptidases (Clegg, 1978;Minagawa et al, 1989) and carboxypeptidases (Umetsu et al, 1983) can be applied successfully. In this context, note that the peptidase activity of the lysed lactic acid bacteria in freshly prepared cheese curd is essential for proper development of the flavor during maturation of cheese (Thomas and Pritchard, 1987).…”
Section: Exopeptidasesmentioning
confidence: 99%